Consumo e desempenho de ovinos alimentados com silagens de cana-de-açúcar tratadas com óxido de cálcio e cloreto de sódio - Rabelo, F. H. S.; Rezende, A. V.; Rabelo, C. H. S. [UNESP]; Nogueira, D. A.; Silva, W. A.; Vieira, P. F.; Santos, W. B. (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2013)
The intake and performance of lambs fed with sugarcane silages treated with whitewash and chloride sodium were evaluated. Seven treatments were used: untreated silage (control); silages treated with 0.5; 1.0 and 1.5% of CaO (whitewash); and silages treated with 0.5; 1.0 and 2.0% of NaCl, with four replicates per treatment. The animals were fed a higher amount of dry matter and total digestible nutrients when the sugarcane silages were treated with 0.5% of NaCl, 1.0 and 1.5% of CaO. The intake of neutral detergent fiber and crude protein increased when the lambs were fed silages treated with 0.5% of NaCl and 1.0% of CaO. The average daily gain did not differ among treatments. The inclusion of 0.5% of sodium chloride and 1.0% of whitewash in sugarcane silages increased the intake and improved the performance of lambs.

Avaliaram-se o consumo e o desempenho de ovinos alimentados com silagens de cana-de-açúcar tratadas com óxido de cálcio (CaO) e cloreto de sódio (NaCl). Utilizaram-se sete tratamentos: controle (silagem sem aditivo), silagens com 0,5; 1,0 e 1,5% de CaO e silagens com 0,5; 1,0 e 2,0% de NaCl, com quatro repetições. Os animais consumiram maior quantidade de matéria seca e de nutrientes digestíveis totais quando se adicionou 0,5% de NaCl ou ainda 1,0 e 1,5% de CaO. Quanto à fibra em detergente neutro e à proteína bruta, observou-se maior consumo quando se adicionou 0,5% de NaCl ou 1,0% de CaO. Não foi observado efeito da dieta sobre o ganho médio diário de peso. A adição de 0,5% de cloreto de sódio e 1,0% de óxido de cálcio à silagem de cana-de-açúcar resultou em aumento no consumo e melhora no desempenho de ovinos.
Intake and performance of lambs fed with sugarcane silages treated with whitewash and sodium chloride
Keywords: Ovino; Aditivo químico; Nutrição; Saccharum officinarum; Lams; Chemical additive; Nutrition; Saccharum officinarum